Functions of Image Transformation in the Poetry of Alisher Navoiy (Zien Journal of Social Sciences and Humanities, 2022)
This article is devoted to the study of the transformation of images and their functions in Alisher Navoi's poetry. It focuses on the literary motifs expressed in the poet's poetry, the classification of lyrical images is studied, and the phenomenon of image migration and change is highlighted as an example of the interpretation of literary symbols. Also, the laws of lyrical expression of literary images and their artistry are discussed.